Hurdle preflight: A case of diminishing returns? - Miller, D. I.; Zecevic, A.; Taylor, G. W. (1999)
The results indicated that HPF techniques are characterized by greater board depression in final approach step support, a shorter final approach step and oscillation of the board tip during the actual flight prior to hurdle support. HPF techniques commonly produced longer hurdle flight times and thus greater downward velocities at the start of takeoff. They were also associated with short hurdles. HPF techniques appear to be more commonly used by female than male divers in elite competition. Answering the challenge of comparing different techniques lies in conducting several studies with each contributing one or more pieces to the puzzle. Our results provided corner pieces to the emerging picture of HPF. The increase in flight time in [1] resulted in <.08 m gain in dive height. Among the divers studied, increase in vertical velocity at the start of the dive, if present, was not functionally significant. Depressing the board in the takeoff depends on a diver`s ability to accelerate upward wrt the board as well as on translational KE from hurdle flight. Sanders & Wilson (1988) indicated that less than 60% of the variance in dive height could be attributed to the latter. Consistent with these observations, the present study suggested that HPF techniques produce diminishing returns in terms of increasing springboard dive height.